Spices sun-dried for two to three days - Mumbai Archive Project Team (Jio Institute, 2024)
Spices purchased at wholesale markets are sun-dried for two to three days to remove moisture. This usually happens once a year in the summer. After the rainy season ends in October, some households may decide to make another batch of masala.